1997
DOI: 10.1055/s-2007-996100
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Risks and Complications in Nephrotic Children

Abstract: The identification of many biologic anomalies is progressively realized in nephrotic children, thanks to adult studies and to scientific advances. The number of anomalies and the intensity of alterations vary from one patient to another and during flare-ups in the same patient. Their severity is usually a function of the severity of the nephrotic syndrome (NS). The responsibility of each anomaly per se in triggering thrombotic complications is not yet known and today it is understood that the coexistence of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
4
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 65 publications
(120 reference statements)
2
106
4
3
Order By: Relevance
“…[3][4][5][6][7] In this study, we have shown that TGA is highly correlated with proteinuria severity and hypoalbuminemia in two commonly used animal models of NS. Furthermore, these studies show that these animals are also hypercoagulable in a proteinuria-and hypoalbuminemia-dependent fashion, with no apparent threshold effect.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…[3][4][5][6][7] In this study, we have shown that TGA is highly correlated with proteinuria severity and hypoalbuminemia in two commonly used animal models of NS. Furthermore, these studies show that these animals are also hypercoagulable in a proteinuria-and hypoalbuminemia-dependent fashion, with no apparent threshold effect.…”
Section: Discussionmentioning
confidence: 66%
“…The coagulation derangements identified in PANnephrotic rats are consistent with previous reports and phenotypically similar to that reported in human NS with respect to hyperfibrinogenemia and AT deficiency. [3][4][5][6]19,20 Thus, the PAN nephrosis model is an excellent preclinical model for the investigation of the acquired hypercoagulopathy of human NS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations